Essential Oil-Loaded Nanofibers for Pharmaceutical and Biomedical Applications: A Systematic Mini-Review - Ioannis Partheniadis; Georgios Stathakis; Dimitra Tsalavouti; Jyrki Heinämäki; Ioannis Nikolakakis (MDPI AG, 2022)
Essential oils (EOs) have been widely exploited for their biological properties (mainly as antimicrobials) in the food industry. Encapsulation of EOs has opened the way to the utilization of EOs in the pharmaceutical and biomedical fields. Electrospinning (ES) has proved a convenient and versatile method for the encapsulation of EOs into multifunctional nanofibers. Within the last five years (2017-2022), many research articles have been published reporting the use of ES for the fabrication of essential oil-loaded nanofibers (EONFs). The objective of the present mini-review article is to elucidate the potential of EONFs in the pharmaceutical and biomedical fields and to highlight their advantages over traditional polymeric films. An overview of the conventional ES and coaxial ES technologies for the preparation of EONFs is also included. Even though EONFs are promising systems for the delivery of EOs, gaps in the literature can be recognized (e.g., stability studies) emphasizing that more research work is needed in this field to fully unravel the potential of EONFs.